How Well Do U.S. Primary Care and Obstetrics and Gynecology Clinicians Screen for Pregnancy Complications at Well Woman Visits? A Retrospective Cohort Study - Eli D. Medvescek; Sorana Raiciulescu; Andrew S. Thagard; Katerina Shvartsman (Korean Society for Preventive Medicine, 2023)
Objectives Pregnancy complications, including pre-eclampsia, gestational diabetes (GDM), and perinatal mood and anxiety disorders (PMADs), impact long-term health. We compared the frequency of screening documentation for pregnancy complications versus a general medical history at well woman visits between providers in primary care and obstetrics and gynecology. Methods We conducted a retrospective cohort study of subjects with at least 1 prior birth who presented for a well woman visit in 2019-2020. Charts were reviewed for documentation of a general medical history (hypertension, diabetes, and mood disorders) versus screening for comparable obstetric complications (pre-eclampsia, GDM, and PMADs). The results were compared using the McNemar and chi-square tests as appropriate. Results In total, 472 encounters were identified, and 137 met the inclusion criteria. Across specialties, clinicians were significantly more likely to document general medical conditions than pregnancy complications, including hypertensive disorders (odds ratio [OR], 2.45; 95% confidence interval [CI], 1.18 to 5.48), diabetes (OR, 7.67; 95% CI, 3.27 to 22.0), and mood disorders (OR, 10.5; 95% CI, 3.81 to 40.3). Obstetrics and gynecology providers were more likely to document any pregnancy history (OR, 4.50; 95% CI, 1.24 to 16.27); however, they were not significantly more likely to screen for relevant obstetric complications (OR, 2.49; 95% CI, 0.90 to 6.89). Overall, the rate of pregnancy complication documentation was low in primary care and obstetrics and gynecology clinics (8.8 and 19.0%, respectively). Conclusions Obstetrics and gynecology providers more frequently documented a pregnancy history than those in primary care; however, the rate was low across specialties, and providers reported screening for clinically relevant complications less frequently than for general medical conditions.